Syncytiotrophoblast Extracellular Vesicles From Late-Onset Preeclampsia Placentae Suppress Pro-Inflammatory Immune Response in THP-1 Macrophages - Awoyemi, Toluwalase; Motta-Mejia, Carolina; Zhang, Wei; Kouser, Lubna; White, Kirsten; Kandzija, Neva; Alhamlan, Fatimah S.; Cribbs, Adam P.; Tannetta, Dionne; Mazey, Emily; Redman, Christopher; Kishore, Uday; et al. (Frontiers in Immunology, 2021)
Syncytiotrophoblast derived Extracellular Vesicles (STBEV) from normal pregnancy (NP) have previously been shown to interact with circulating monocytes and B cells, and induce pro-inflammatory cytokine release. Early-onset preeclampsia (EOPE) is associated with an exacerbated inflammatory response, yet there is little data regarding late-onset PE (LOPE) and immune function. Here, using a macrophage/monocyte cell line THP-1, we investigated the inflammatory potential of STBEV, comprising medium/large-STBEV (>200nm) and small-STBEV (<200nm), isolated from LOPE (n=6) and normal (NP) (n=6) placentae via dual-lobe ex-vivo placental perfusion and differential centrifugation. THP-1 cells bound and internalised STBEV isolated from NP and LOPE placentae, as revealed by flow cytometry, confocal microscopy and ELISA. STBEV-treated THP-1 cells were examined for cytokine gene expression by RT-qPCR and the cell culture media examined for secreted cytokines/chemokines. As has been previously reported, NP medium/large-STBEV significantly upregulated the transcriptional expression of TNF-α, IL-10, IL-6, IL-12, IL-8 and TGF-β compared to PE medium/large-STBEV, however, there was no significant difference in the small STBEV population between the two groups though in general, NP small STBEVs slightly upregulated the same cytokines. In contrast, LOPE STBEV (medium and large) did not induce pro-inflammatory responses by differentiated THP-1 macrophages. This decreased effect of LOPE STBEV was echoed in cytokine/chemokine release. Our results appear to suggest that STBEV from LOPE placentae do not have a major immune-modulatory effect on macrophages. In contrast, NP STBEV caused THP-1 cells to release pro-inflammatory cytokines. Thus, syncytiotrophoblast extracellular vesicles from LOPE dampen immune functions of THP-1 macrophages, suggesting an alternative mechanism leading to the pro-inflammatory environment observed in LOPE.